Preparation of fluorinated polyimides with bulky structure and their gas separation performance correlated with microstructure. (9th July 2015) - Tong, Hui; Hu, Chenchen; Yang, Shiyong; Ma, Yanping; Guo, Hongxia; Fan, Lin
Abstract: The fluorinated polyimides with high fractional free volume were prepared from 6FDA and aromatic diamines with bulky triptycene and pendent phenyl moieties. These polymers showed excellent solubility, high thermal stabilities and outstanding mechanical properties. The correlation of gas separation performance with the microstructure of these polyimide membranes was investigated. The results indicated that the GSPI-P membranes based on the diamines with pendent phenyl moieties exhibited higher fractional free volumes than GSPI-T membranes derived from diamines with triptycene moieties; as a result, the former gave the much higher permeability coefficients. The gas permeability of these membranes is strongly depended on their free volume and also affected by fluorine content. The GSPI-P membranes also provided good selectivity for CO2 /CH4 and CO2 /N2 gas pairs because their appropriate cavity size is favorable to separate the CO2 from the other gases. Graphical abstract: Highlights: The fluorinated polyimides were synthesized from dianhydride 6FDA and aromatic diamines with bulky triptycene and pendent phenyl moieties. The polyimide membranes, especially the GSPI-P ones revealed outstanding permeability coefficients combined with good selectivity especially for CO2 /CH4 separation. Large quantity of free volume combined with appropriate cavity size in polymeric membranes is beneficial to improve their permeability and selectivity simultaneously.